Minimum Wage and Unemployment: An Empirical Study on OECD Countries - Kim, Chong Uk; Lim, Gieyoung (Journal of Reviews on Global Economics, 2018)
With ongoing increasing minimum wage and political debates underway, minimum wage and its impacts on the labor market are one of the most important items on policymakers' agendas worldwide. In this paper, we attempt to explain how labor demand and supply respond to minimum wage increases. In our model, firms can hire either skilled or unskilled workers to maximize their profits. With data from 25 OECD countries over 15 years from 2000 to 2014, we find that a higher minimum wage decreases labor demand but does not affect labor supply. Our empirical results also suggest that relatively modest increases in minimum wages have limited impacts on employment. On average, 10 percent increase in the minimum wage decreases employment by 0.7 percent, thereby increasing unemployment rate by 0.64 percent.